DOKUMENTER EKSPOSITORI “RESONANCE OF CHANGE” - Nanda, Putu Arya Dhamma; Dwiyani, Ni Kadek; Pandet, Putu Raditya (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
The production of the short documentary film Resonance of Change was created to observe the process of social adaptation of individuals in facing new environments. This film explored the changes in individual attitudes before and after adapting to their new surroundings, highlighting how social and cultural factors influenced their attitudes and identities. The documentary aimed to provide an in-depth insight into the dynamics of adaptation, focusing on the social, cultural, and emotional aspects involved in the process. With an expository approach, the narrative was presented in an informative and objective manner through interviews and direct observations, encouraging the audience's understanding of social attitude changes as a form of adaptation in daily life. The creation of this work involved partners and institutions to ensure the project had lasting benefits. This documentary project was chosen because it presented the story and information in an engaging format—film. It was also selected after extensive research, which concluded that the topic being addressed was very important and should be shared with the public in an interesting way.